2023
DOI: 10.1002/ps.7432
|View full text |Cite
|
Sign up to set email alerts
|

Leptosphaeria maculans isolates with variations in AvrLm1 and AvrLm4 effector genes induce differences in defence responses but not in resistance phenotypes in cultivars carrying the Rlm7 gene

Abstract: BACKGROUNDThe phoma stem canker pathogen Leptosphaeria maculans is one of the most widespread and devastating pathogens of oilseed rape (Brassica napus) in the world. Pathogen colonization is stopped by an interaction of a pathogen Avr effector gene with the corresponding host resistance (R) gene. While molecular mechanisms of this gene‐for‐gene interaction are being elucidated, understanding of effector function remains limited. The purpose of this study was to determine the action of L. maculans effector (Av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…29 However, it has been also demonstrated that although AvrLm1 and AvrLm4 effector genes induce differences in defense responses, it is not the case in cultivars carrying the Rlm7 gene. 30 To date, two genetic subclades of L. maculans ('brassicae' and 'lepidii') and seven subclades of L. biglobosa ('americensis', 'australensis', 'brassicae', 'canadensis', 'erysimii', 'occiaustralensis' and 'thlaspii') have been identified, leaving unsolved the problem of distinguishing the spores of these forms when they constitute the inoculum contained in the air. Fortunately, the efficiency and specificity of the qPCR method using SYBR-Green and primers described in the literature were compared, and primers detecting both species were selected, including P. biglobosus subclade 'canadensis' as well as P. dezfulensis, a unique species infecting rapeseed in Iran, which may also become a part of air-transmitted spores.…”
Section: Integrated Pest Control In Oilseed Crops-new Advances From T...mentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, it has been also demonstrated that although AvrLm1 and AvrLm4 effector genes induce differences in defense responses, it is not the case in cultivars carrying the Rlm7 gene. 30 To date, two genetic subclades of L. maculans ('brassicae' and 'lepidii') and seven subclades of L. biglobosa ('americensis', 'australensis', 'brassicae', 'canadensis', 'erysimii', 'occiaustralensis' and 'thlaspii') have been identified, leaving unsolved the problem of distinguishing the spores of these forms when they constitute the inoculum contained in the air. Fortunately, the efficiency and specificity of the qPCR method using SYBR-Green and primers described in the literature were compared, and primers detecting both species were selected, including P. biglobosus subclade 'canadensis' as well as P. dezfulensis, a unique species infecting rapeseed in Iran, which may also become a part of air-transmitted spores.…”
Section: Integrated Pest Control In Oilseed Crops-new Advances From T...mentioning
confidence: 99%
“…Large‐scale population surveys of L. maculans done in France highlighted both on‐going breakdowns and potentially effective resistance genes in OSR 29 . However, it has been also demonstrated that although AvrLm1 and AvrLm4 effector genes induce differences in defense responses, it is not the case in cultivars carrying the Rlm7 gene 30 . To date, two genetic subclades of L. maculans (‘brassicae’ and ‘lepidii’) and seven subclades of L. biglobosa (‘americensis’, ‘australensis’, ‘brassicae’, ‘canadensis’, ‘erysimii’, ‘occiaustralensis’ and ‘thlaspii’) have been identified, leaving unsolved the problem of distinguishing the spores of these forms when they constitute the inoculum contained in the air.…”
mentioning
confidence: 99%